Assessment of heat mitigation capacity of urban greenspaces with the use of InVEST urban cooling model, verified with day-time land surface temperature data - Zawadzka, Joanna Ewa; Harris, Jim A.; Corstanje, Ronald (Elsevier, 2021)
Accurate quantification of the heat mitigation capacity of urban greenspaces is essential in planning decisions due to increased thermal pressures on existing and new urban environments associated with climate change. However, this often requires data analytical skillsets that may not be available to the planning community. The recently developed InVEST 3.8.7 Urban Cooling model addresses this limitation by using several easily accessible parameters, assigned to a land cover map, to produce a heat mitigation index (HMI) intended to estimate the cooling capacity of vegetation in a spatial context. In this study, we validated the HMI derived for three towns with differing morphologies by comparison to land surface temperature (LST) data using linear regression analysis. We found that the HMI can be used to explain a variable proportion of the variation in LST, with R2 ranging from 0.48 to 0.64 depending on the town, with stronger associations obtained for towns with a higher range of LST values. Higher resemblance to LST data was achieved after resampling of the 2 m resolution model outputs to 30 m resolution, inclusion of water bodies as cooling features, and using cooling distance away from large greenspaces of 100 m. On average, a change in the HMI of 0.1 was associated with 0.76 °C change in LST. We conclude that the model is suitable for assessment of heat mitigation interventions through incorporation of vegetation and water bodies into city plans at scales relevant to masterplans rather than fine-tuning of urban design.
Keywords: InVEST Urban Cooling model; Urban heat island; Heat mitigation; Land surface temperature